2016
DOI: 10.3892/mmr.2016.5771
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide isolated from the liquid culture broth of Inonotus obliquus suppresses invasion of B16-F10 melanoma cells via AKT/NF-κB signaling pathway

Abstract: A number of polysaccharides exhibit pharmacological activities. Polysaccharides derived from Inonotus obliquus (PLIO) appear to have various potential pharmacological properties, including anti‑tumor activity. However, the molecular mechanisms underlying these properties remain to be elucidated. The present study investigated the anti‑metastatic potential of PLIO and the underlying signaling pathways in B16‑F10 murine melanoma cells using the MTT colorimetric assay, in vitro migration and invasion assays, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Lee found that IOPS can effectively inhibit the migration and invasion of human non-small cell lung cancer A549 cells. Its possible mechanism might be that IOPS inhibits NF-κB nuclear translocation and JNK/AKT phosphorylation in A549 cells, and inhibits the AKT/NF-κB signaling pathway that reduces the expression level of matrix metalloproteinases (MMP); therefore, the invasion of human non-small cell lung cancer A549 cells was inhibited [ 96 , 97 ].…”
Section: Biological Activitymentioning
confidence: 99%
“…Lee found that IOPS can effectively inhibit the migration and invasion of human non-small cell lung cancer A549 cells. Its possible mechanism might be that IOPS inhibits NF-κB nuclear translocation and JNK/AKT phosphorylation in A549 cells, and inhibits the AKT/NF-κB signaling pathway that reduces the expression level of matrix metalloproteinases (MMP); therefore, the invasion of human non-small cell lung cancer A549 cells was inhibited [ 96 , 97 ].…”
Section: Biological Activitymentioning
confidence: 99%
“…The same authors proposed a similar mechanism (MAPKS, COX-2 and NF-κB pathway) on direct in vitro anti-migration, anti-invasion, and anti-proliferation activity on B16-F10 mouse melanoma cells (Lee et al, 2014b). However, the same authors later refuted their own proposed antimigration ability (Lee et al, 2016). While in vitro trial of LLC1 cell, the purified chaga polysaccharide showed direct cytotoxicity for activating AMPK via phosphorylation of threonine 172 by LKB1, downregulating Bcl-2 and upregulating Bax, as well as enhancing cleavage of Caspase-3 and PARP, leading to the opening of mitochondrial permeability transition pore, and reducing MMP, eventually resulting in an inhibition of ATP production and cellular proliferation (Jiang et al, 2019).…”
Section: )mentioning
confidence: 97%
“… 109 Moreover, it has been reported that I. obliquus polysaccharides inhibit the expression of MMP-2, MMP-7, and MMP-9 in B16–F10 mouse cells. 93 Recently, Zhang et al. described that inotodiol from I. obliquus decreases the expression of MMP-2 and MMP-9 in HeLa human cells and reduces cell invasiveness.…”
Section: Biological Properties Of Inonotus Obliquus Extractsmentioning
confidence: 99%